Contribution of food sources to the vitamin B12 status of South Indian children from a birth cohort recruited in the city of Mysore. Issue 4 (27th May 2014) - Christian, Anna M; Krishnaveni, Ghattu V; Kehoe, Sarah H; Veena, Sargoor R; Khanum, Rumana; Marley-Zagar, Ella; Edwards, Phil; Margetts, Barrie M; Fall, Caroline HD
Abstract Objective There is evidence that subclinical vitamin B12 (B12) deficiency is common in India. Vegetarianism is prevalent and therefore meat consumption is low. Our objective was to explore the contribution of B12-source foods and maternal B12 status during pregnancy to plasma B12 concentrations. Design Maternal plasma B12 concentrations were measured during pregnancy. Children's dietary intakes and plasma B12 concentrations were measured at age 9·5 years; B12 and total energy intakes were calculated using food composition databases. We used linear regression to examine associations between maternal B12 status and children's intakes of B12 and B12-source foods, and children's plasma B12 concentrations. Setting South Indian city of Mysore and surrounding rural areas. Subjects Children from the Mysore Parthenon Birth Cohort (n 512, 47·1 % male). Results Three per cent of children were B12 deficient (<150 pmol/l). A further 14 % had 'marginal' B12 concentrations (150–221 pmol/l). Children's total daily B12 intake and consumption frequencies of meat and fish, and micronutrient-enriched beverages were positively associated with plasma B12 concentrations (P=0·006, P=0·01 and P=0·04, respectively, adjusted for socio-economic indicators and maternal B12 status). Maternal pregnancy plasma B12 was associated with children's plasma B12 concentrations, independent of current B12 intakes (P<0·001). Milk and curd (yoghurt) intakes were unrelated to B12 status. Conclusions Meat and fish are important B12 sources in this population. Micronutrient-enriched beverages appear to be important sources in our cohort, but their high sugar content necessitates care in their recommendation. Improving maternal B12 status in pregnancy may improve Indian children's status.